Government Bureaucracy Ethics In Perspective Neoclassical Political Economy - Eli Apud Saepudin; Ita Rosita Wahyiah (Journal of Politica Governo, 2024)
Neoclassical political economy, a pivotal school of economic thought, has shaped our understanding of economics while facing criticism. Dominating the global stage, it accentuates free markets and the price mechanism's role in resource allocation. Despite its influence, this school isn't immune to scrutiny, particularly regarding government bureaucratic ethics—the moral compass guiding state apparatus behavior. Upholding strong foundational principles, it encounters disapproval regarding its stance on ethical governance. Government bureaucracy's ethical framework is crucial for fostering public trust, prompting ongoing debate within the neoclassical paradigm. While revered for its insights, this school grapples with the challenge of aligning economic theory with ethical imperatives in governance. Balancing market dynamics with ethical considerations remains a perpetual task, underscoring the complexity of neoclassical political economy's role in contemporary discourse.